The social cost of small families and land reform : a case study of the Wataita of Kenya - Mkangi, George C. (International population series, 1983)
A convincing argument against the widespread belief that rapid population growth is an obstacle to socio-economic development, while individual land ownership is a prerequisite. The author presents an in-depth study of traditional land tenure in Taita, Kenya, where the implementation of birth control programmes and the individualization of land tenure have failed to eradicate rural poverty and have brought about other sociopsychological problems. This book is of vital importance to development personnel to help them place the problem of population growth in its proper perspective.